Exploring the molecular mechanisms and immune cell responses in brucellosis: Insights from gene expression profiles and immune cell scores - Xiaoyuan Hu; Yuefei Li; Jiangshan Zhao; Yahetikezi Muhedaner; Kai Yang; Mengzhen Dong; Mukedaisi Aihemaijiang; Shuqin Lei; Jingxuan Sun (PLoS ONE, 2025)
Background Brucellosis is a typical zoonotic disease. The study aimed to identify key molecular markers and immune cell imbalances in brucellosis by integrating transcriptomic profiling, co-expression network analysis, and immune cell scoring. Methods Gene expression profile of 103 patients with brucellosis and 46 healthy controls were obtained from the GSE69597 dataset. Differential analysis was conducted on gene expression and immune cell score, followed by co-expression network construction. Diagnostic value of module genes was assessed using Gradient Boosting Machine (GBM) and Random Forest (RF) models to screen marker genes. Peripheral blood samples from 88 brucellosis patients and 70 healthy individuals were collected for validation using flow cytometry, RT-qPCR and Western blot. Results A total of 4924 DEGs were identified, and 11 co-expression modules were constructed. The Brown module showed the highest positive correlation with normal controls, while the Greenyellow module had the highest negative correlation. Enrichment analysis revealed that genes in the Brown module were mainly involved in the cell cycle and virus infection, genes in the Greenyellow module were primarily associated with the PI3K-Akt and Wnt signaling pathway. CDK1, MAPK11, and PDIA3 were identified as marker genes with high importance in both models. The marker genes were significantly higher expression in brucellosis. CD8 + T cells and NK cells were higher in brucellosis than in the control group, whereas B cells and CD4 + T cells were lower, which was confirmed by flow cytometry. Conclusion The abnormal levels of CDK1, MAPK11, PDIA3, and immune cells in brucellosis may be involved in the disease’s pathogenic mechanisms.